Theo started to solve the quadratic equation (x + 2)^2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)^2 = 4. Next, he took the square
Mathematics
ashly123
Question
Theo started to solve the quadratic equation (x + 2)^2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)^2 = 4. Next, he took the square root of each side. Which was the resulting equation of that step?
x + 2 = ±4
x + 2 = ±2
x + 2 = ±8
x + 2 = ±16
x + 2 = ±4
x + 2 = ±2
x + 2 = ±8
x + 2 = ±16
2 Answer
File Size: 23.8 MB
File Type: PDF / ePub
Uploaded on: 20240118 05:10:00
READ ANOTHER ANSWER
Last checked: 1 hours 14 minutes ago!
Rating: 4.6/5 from 2955 votes.

1. User Answers Billymkhoi
When we take the square root of each side, the equation would become:
abs (x+2) = 2
⇒ x+2 = ±2.
The final answer is x + 2 = ±2.
Hope this helps~ 
2. User Answers AL2006
The square root of (x + 2)² is (x + 2) .
The square roots of 4 are +2 and 2 .
So the resulting equation was x + 2 = ± 2 .
From there, it was pretty easy for Theo to find the solutions
to the original equation . . .
If (x + 2) = +2 , then x = 0 .
If (x + 2) = 2 , then x = 4 .